Sudden cardiac arrest in people with epilepsy in the community: Circumstances and risk factors - Lamberts, Robert J. (Neurology, 2015)
OBJECTIVE: To ascertain whether characteristics of ventricular tachycardia/fibrillation (VT/VF) differed between people with epilepsy and those without and which individuals with epilepsy were at highest risk. METHODS: We ascertained 18 people with active epilepsy identified in a community-based registry of sudden cardiac arrest (SCA) with ECG-confirmed VT/VF (cases). We compared them with 470 individuals with VT/VF without epilepsy (VT/VF controls) and 54 individuals with epilepsy without VT/VF (epilepsy controls). Data on comorbidity, epilepsy severity, and medication use were collected and entered into (conditional) logistic regression models to identify determinants of VT/VF in epilepsy. RESULTS: In most cases, there was an obvious (10/18) or presumed cardiovascular cause (5/18) in view of preexisting heart disease. In 2 of the 3 remaining events, near–sudden unexpected death in epilepsy (SUDEP) was established after successful resuscitation. Cases had a higher prevalence of congenital/inherited heart disease (17% vs 1%, p = 0.002), and experienced VT/VF at younger age (57 vs 64 years, p = 0.023) than VT/VF controls. VT/VF in cases occurred more frequently at/near home (89% vs 58%, p = 0.009), and was less frequently witnessed (72% vs 89%, p = 0.048) than in VT/VF controls. Cases more frequently had clinically relevant heart disease (50% vs 15%, p = 0.005) and intellectual disability (28% vs 1%, p < 0.001) than epilepsy controls. CONCLUSION: Cardiovascular disease rather than epilepsy characteristics is the main determinant of VT/VF in people with epilepsy in the community. SCA and SUDEP are partially overlapping disease entities.